2023
DOI: 10.55927/mudima.v3i6.3012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insurance Literation, Perceived Product Benefits, Trust in Insurance & Perceived Product Risk on Decision to Purchase Personal Insurance

Abstract: In this study, it is suspected that there are several factors that can influence the intention to purchase personal insurance. These factors are consumer insurance literacy, perceived product benefits, trustworthiness in insurance, perceived product risk, and favorable attitude towards personal insurance, so this research was conducted to determine whether there is an effect of these variables on the intention to buy insurance. This study uses Structural Equation Modeling (SEM) analysis with AMOS 24 software, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Fourth, people feel they are very careful in every action, so they do not feel the need for insurance. Fifth, people have the assumption that insurance claims are difficult (Dewi, 2023). From the statements and data on private health insurance, it can be concluded that public interest in purchasing independent private health insurance is still an obstacle for the people of Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, people feel they are very careful in every action, so they do not feel the need for insurance. Fifth, people have the assumption that insurance claims are difficult (Dewi, 2023). From the statements and data on private health insurance, it can be concluded that public interest in purchasing independent private health insurance is still an obstacle for the people of Indonesia.…”
Section: Introductionmentioning
confidence: 99%